Sustainability assessment for crude palm oil production in Malaysia using the palm oil sustainability assessment framework - Lim, C.; Biswas, Wahidul (Wiley InterScience, 2018)
The sustainability of production is one of the greatest challenges experienced by the Malaysian palm oil industry. Palm oil products consistently receive negative press and criticism, for causing deforestation, land use changes, peat land conversion, species loss, greenhouse gas emissions, biomass waste generation, violation of indigenous people's rights and limited local employment. This paper evaluates the sustainability of the most common crude palm oil supply chain in Malaysia, located in Sarawak, using the Palm Oil Sustainability Assessment (POSA) framework. The results show that the overall sustainability score for a typical crude palm oil supply chain in Malaysia is 3.47/5, which is below the sustainability target of 5/5. Hotspots identified include smallholder inequity, lack of biomass waste recycling and recovery, improper plantation practices, lower average wages and local employment. The site‐specific application of the POSA framework in the current study demonstrates its potential to be used universally across Malaysia.